AE Characteristics of Rockburst Tendency for Granite Influenced by Water Under Uniaxial Loading - Zhang, Yihan; Ma, Ju; Sun, Daoyuan; Zhang, Lingyun; Chen, Yongchao (Frontiers in Earth Science, 2020)
In deep mining, granite is stored with high energy duing to its structural integrity and brittleness. Rock bursts usually occur because stress changes and mining disturbances during mining, which seriously threaten safe production. Focusing on the factor -water- which may reduce the brittleness and rockburst tendency of granite, this paper quantitatively analyzes the brittleness index and AE characteristics of dry and water granite under uniaxial loading. The results show that the peak strength and elastic modulus of the water granite are reduced. The damage degree of the water sample is larger than that of the dry sample, and the brittle failure is significantly reduced. The cumulative number of acoustic emission (AE) events in water granite is significantly reduced compared to the dry sample, which is a decrease of 31.5%. However, AE event rate is higher than that of dry granite in the late loading period; AE quiet period of water granite lasts longer and is more obvious than that of dry granite. Dry granite stores and releases more energy during the whole loading process, and the proportion of high energy level AE events in the later stage of loading is higher. The b value of the two samples show a downward trend with fluctuation in the critical state of fracture and a jump increases at the moment of instability. The decrease of b values of dry granite is larger than that of water granite. Results prove that the decline of AE b value of granite can be taken as the precursor of rock burst, and water can significantly reduce the rock burst tendency of granite.